Women's empowerment through political participation in India - Fadia, Kuldeep (2014)
The ethics and trend of participatory aspect has been advocated in this article for vibration of universal trend of understanding in realism. The data and indicators in this artcle symbolise the phenomenon of growth and attributes in the sphere of political participation of women for holistic mindset and political stratification on the highest cohesive sense of the term and conditionalities. - Reproduced.
Keywords: Political participation - India; Women in politics - India; Women in politics